The impact of land use changes on the riverine enviroment of Liwagu-Labuk river basin in Sabah - Choo, Agatha Mui Sien (Universiti Malaysia Sarawak (UNIMAS), 2003)
The impact of land use changes on the riverine environment ofthe Liwagu-Labuk River Basin has been studied. Intensification of several land use activities such as agricultural, tourism, industrial and settlements have led to competition for water and land resources among the stated sectors. Deterioration of the river water quality has been affirmed through declining water quality index (WOI) or river class category and increased suspended sediment loading. For most of the monitoring stations} water quality parameters are within the DOE specified range for Class II river though occasionally deteriorated to Class III for those located at the downstream. The suspended sediment loading in the river has increased significantly, from 215.4 mg/L (in 1971-1980) to 434.6 mg/L (in 1993-2000), which is approximately twice of the earlier record. Literature search, interview, ground survey, river classification and comparison between previous and current land uses have been employed for this study_ Briefly, it is apparent that the effects of unplanned development activities would be the degradation of the environment} as for this study is the declining river water quality caused by total suspended solids (TSS).